Biofertilization with Trichoderma strains on nutrition of quinoa (Chenopodium quinoa willd) Salcedo INIA under greenhouse (Bioagro, 2023)
Quinoa is a crop with high economic and social potential in the Puno Region, Peru; however, its production is affected by low soil fertility. One way to deal with this problem, without affecting the environment, is through the use of beneficial microorganisms. The objective of the study was to evaluate the effect of Trichoderma sp. on N, P and K levels in plants and soil. The research was carried out in the Phytopathology Laboratory and greenhouse of the Professional School of Agricultural Engineering in the city of Puno, from January to July 2015. Five strains of Trichoderma sp. were inoculated in quinoa var. Salcedo-INIA plants by soil application or using pelleted seed. At the end of the crop cycle (six months), the levels of N, P and K were evaluated both in the plant tissue and in soil. No effects of Trichoderma inoculation on soil nutrient levels were detected, but the inoculated plants showed higher P and K contents than the control (p≤0.05). The results did not support the thesis of the solubilizing effect of Trichoderma on soil nutrients, but support the idea that the plant improved its efficiency in nutrient absorption attributed to the greater growth of the root system.
Keywords: Beneficial microorganisms; nitrogen; phosphorus; potassium; soil fertility